Practical knowledge of elite female kendoists: Focusing on tactics of the most accomplished - Takenaka, M.; Aida, H.; Sasaki, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2024)
This study aimed to clarify the reality of female Kendo players` tactical actions with their signature techniques. Apropos this, we conducted interviews with three female kendo player who had competed at the international level, and analyzed their narratives qualitatively. Our findings were as follows: